Surface treatment method and device for high-filling polymer hollow plate
By using hot pressing, plasma cleaning, nanocomposite primer curing, and laser processing, the problem of insufficient adhesion of high-filled polymer hollow boards was solved, and the adhesion and overall performance of the coating were improved.
Patent Information
- Application Number
- CN202511095452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-11-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the adhesion of high-filled polymer hollow plates is insufficient, which affects their optical properties and the adhesion performance of coatings.
A dense surface layer is formed through hot pressing, surface energy is increased through plasma cleaning, a nano-composite primer is applied and cured in two stages, and finally laser processing is performed to form microstructures and melting ripples.
It significantly improves the adhesion, durability and overall performance of the coating, enhances the surface corrosion resistance and oxidation resistance, and improves the visual effect and physical properties.
Smart Images

Figure CN120961403A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of surface treatment technology, and in particular to a surface treatment method and apparatus for a high-filling polymer hollow plate. Background Technology
[0002] High-filled polymer hollow core sheets are typically composed of a polymer matrix (such as polypropylene (PP), polyethylene (HDPE), or polycarbonate (PC)) and a large amount of fillers (such as calcium carbonate, talc, etc.). As a lightweight, high-strength composite material, high-filled polymer hollow core sheets have been widely used in logistics packaging, automotive manufacturing, and building decoration due to their excellent specific strength, low cost, and designability. With the continuous growth of market demand, the requirements for the performance, durability, and appearance of high-filled polymer hollow core sheets are also increasing.
[0003] In the prior art, during the production process of polymer hollow boards, the addition of filler materials often leads to insufficient surface smoothness, which in turn affects their optical properties and adhesion performance, resulting in insufficient adhesion of coatings, adhesives and other materials. Summary of the Invention
[0004] The purpose of this invention is to provide a surface treatment method and apparatus for high-filled polymer hollow boards, which solves the technical problem of insufficient adhesion of high-filled polymer hollow boards in the prior art.
[0005] To achieve this objective, the present invention adopts the following technical solution: According to a first aspect, the present invention provides a surface treatment method for a highly filled polymer hollow plate, comprising: Step S1: Provide a high-filled polymer hollow board and perform hot pressing on the high-filled polymer hollow board to form a dense surface layer with a thickness of 50~100μm. Step S2: The hot-pressed high-fill polymer hollow plate is subjected to plasma cleaning to improve the surface energy of the high-fill polymer hollow plate. Step S3: A nanocomposite primer is coated on the surface of the plasma-cleaned high-fill polymer hollow plate to obtain a first coating with a thickness of 5~8μm; wherein, the nanocomposite primer includes epoxy-polyurethane hybrid resin and nano-silica modified with silane coupling agent. Step S4: Perform a two-stage curing process on the first coating; wherein the two-stage curing includes pre-curing and UV curing; Step S5: Apply a functional topcoat to the surface of the cured first coating to obtain a functional coating, and then cure the functional coating; wherein the functional coating includes a second coating, a third coating, and a fourth coating attached in sequence. Step S6: Perform laser processing on the functional coating to form microstructures and melting ripples on the surface of the functional coating.
[0006] Optionally, step S1 includes: Step S11: The high-filled polymer hollow board is placed in a two-roller hot pressing system and hot-pressed by the hot pressing rollers; wherein, the surface of the hot pressing rollers is coated with polytetrafluoroethylene, the roller surface temperature is 10~15°C below the melting temperature of the substrate polymer, the pressure is controlled at 0.5~1.2MPa, and the contact time is 3~8s; Step S12: The roller spacing is dynamically adjusted by a servo pressure control system to form a dense surface layer with a thickness of 50~100μm on the surface of the high-fill polymer hollow board; wherein the surface roughness Ra of the dense surface layer is ≤0.8μm.
[0007] Optionally, after step S12, step S1 further includes: Step S13: The hot-pressed high-fill polymer hollow board is rapidly cooled and shaped using a water-cooled roller; wherein the cooling water temperature of the water-cooled roller is 15~25℃ and the cooling rate is ≥50℃ / s.
[0008] Optionally, step S2 specifically includes: The hot-pressed high-fill polymer hollow plate is placed in an atmospheric pressure plasma treatment device, and the surface of the high-fill polymer hollow plate is cleaned by argon plasma; wherein the argon flow rate is 20~50L / min, the plasma power is 800~1200W, the treatment distance is 5~10mm, and the treatment time is 30~90s.
[0009] Optionally, step S3 includes: Step S31: Silane coupling agent-modified nano-silica with a particle size of 20-50 nm is dispersed in a solvent at a ratio of 3-5 wt% to form a nano-composite primer; the epoxy-polyurethane hybrid resin has a solid content of 40-50%. Step S32: The nanocomposite primer is applied to the surface of the plasma-cleaned high-fill polymer hollow plate using an ultrasonic-electrostatic atomization spraying device to form a first coating with a thickness of 5~8μm; wherein the spraying voltage is 25~35kV, the ultrasonic frequency is 25~30kHz, the spraying distance is 15~25cm, the atomization angle is 60~80°, and the atomization pressure is 0.2~0.4MPa.
[0010] Optionally, after step S32, the method further includes: Step S33: After the nano-composite primer is applied, the first coating is leveled to eliminate ripples or bubbles generated during the spraying process; wherein the leveling temperature is 40~60℃, the leveling time is 30~60s, and the humidity is controlled at 30~50%RH.
[0011] Optionally, step S4 includes: Step S41: The high-filling polymer hollow board coated with the first coating is pre-cured in a hot air circulating curing box to achieve a curing degree of 70-80% for the nano-composite primer; wherein the curing temperature is 80℃±2℃ and the curing time is 1.5-2.5min. Step S42: The pre-cured first coating is UV-cured using a dual-wavelength UV light source to achieve a final curing degree of ≥95%; wherein, in the first stage, a UV light source with a wavelength of 365nm and an energy density of 200~300mJ / cm² is used. 2 The irradiation time is 5-8 seconds; the second stage uses a UV light source with a wavelength of 420 nm and an energy density of 500-800 mJ / cm². 2 The irradiation time is 10-15 seconds.
[0012] Optionally, step S5 includes: Step S51: Electrostatically spray fluorinated polyurethane acrylate resin onto the surface of the cured first coating to form a second coating with a thickness of 10~15μm; wherein the spraying voltage is 40~60kV, the spraying flow rate is 50~80mL / min, and the coating is allowed to stand and level for 1~2 minutes after spraying. Step S52: Spin-coat nano-Al2O3-reinforced organosilicon modified resin onto the surface of the second coating to form a third coating with a thickness of 8~12μm, and perform a thermosetting treatment on the third coating; wherein, the spin-coating speed is 800~1200rpm, the curing temperature is 100~120℃, and the curing time is 3~5min. Step S53: Photochromic titanium dioxide / graphene composite slurry is applied to the surface of the third coating through slit extrusion to form a fourth coating with a thickness of 5~8μm; wherein the coating gap is 50~100μm and the coating speed is 2~4m / min. Step S54: A functional coating including a second coating, a third coating, and a fourth coating is obtained. The functional coating is then subjected to gradient curing treatment using a three-wavelength UV light source.
[0013] Optionally, step S6 includes: Step S61: A femtosecond fiber laser is used to laser-etch the functional coating to form a periodic array of micron-sized grooves on the surface of the fourth coating; wherein the depth of the grooves is 5~15μm, the width is 20~50μm, and the spacing between adjacent grooves is 50~100μm. Step S62: Switch the femtosecond fiber laser to quasi-continuous mode and use a flat-top laser spot to perform melting and regeneration treatment on the engraved area, forming nanoscale melting ripples with a height difference ≤0.5μm; wherein the laser power density is 2~5×10 4 W / cm 2 The scanning speed is 200~400mm / s; Step S63: A helium / nitrogen mixed cooling gas is introduced to cool the functional coating after laser processing; wherein the volume ratio of helium to nitrogen is 1:4.
[0014] According to a second aspect, the present invention provides a surface treatment apparatus for a high-filling polymer hollow board, applied to the surface treatment method for a high-filling polymer hollow board as described in the first aspect, comprising a dual-roller hot pressing module, a plasma cleaning module, a coating module, a curing module, a functional processing module, and a laser processing module; wherein the dual-roller hot pressing module comprises a hot pressing roller and a cold pressing roller; The dual-roller hot pressing module is used to perform hot pressing on the high-filled polymer hollow board; the plasma cleaning module is used to perform plasma cleaning on the high-filled polymer hollow board after hot pressing; the coating module is used to coat the surface of the plasma-cleaned high-filled polymer hollow board with a nano-composite primer to obtain a first coating layer; and the curing module is used to cure the first coating layer. The functional processing module is used to coat the surface of the first coating after curing with a functional topcoat to obtain a functional coating, and to cure the functional coating; the laser processing module is used to perform laser processing on the functional coating to form microstructures and melting ripples on the surface of the functional coating.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a surface treatment method and apparatus for high-filled polymer hollow boards. Step S1 involves hot pressing to form a dense layer with a thickness of 50-100 μm on the surface of the high-filled polymer hollow board, significantly reducing surface porosity, improving the mechanical strength and surface smoothness of the substrate, and providing a uniform and stable adhesion substrate for subsequent coatings. Step S2 involves plasma cleaning, which significantly increases the surface energy of the high-filled polymer hollow board, enhancing the adhesion between the coating and the substrate, providing a good surface foundation for subsequent application of a nanocomposite primer, thereby improving the durability and adhesion of the coating. In step S3, the application of the nanocomposite primer not only further enhances the surface corrosion resistance and oxidation resistance but also helps improve the overall performance of the high-filled polymer hollow board. Step S4 involves a two-stage curing process, effectively avoiding uneven coating surface and bubble problems, ensuring the degree of curing, and improving the durability and performance stability of the coating. In step S5, the application of a multi-layered functional coating enables the high-filled polymer hollow board to possess multiple functions during use, increasing the product's application range and market competitiveness. In step S6, the microstructure and melting ripples after laser processing not only improve the visual effect of the coating but also enhance the physical properties of the coating surface (such as the coefficient of friction and optical properties), thereby improving the applicability of the high-filled polymer hollow board in special application fields. Therefore, the present invention solves the technical problem of insufficient adhesion of high-filled polymer hollow boards in the prior art. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] The structures, proportions, sizes, etc., shown in the accompanying drawings of this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed in the specification, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.
[0018] Figure 1 This is a schematic flowchart of a surface treatment method for a high-filling polymer hollow plate provided in Embodiment 1 of the present invention; Figure 2 This is a schematic diagram of the surface treatment device for a high-filling polymer hollow plate provided in Embodiment 2 of the present invention. Detailed Implementation
[0019] To make the objectives, features, and advantages of this invention more apparent and understandable, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0020] In the description of this invention, it should be understood that the terms "upper," "lower," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. It should be noted that when a component is considered to be "connected" to another component, it can be directly connected to the other component or there may be a component positioned centrally in the connection.
[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0022] Example 1: This invention provides a surface treatment method for highly filled polymer hollow plates, comprising: Step S1 involves providing a highly filled polymer hollow board and hot-pressing it to form a dense surface layer with a thickness of 50-100 μm. This dense surface layer improves the surface quality and performance. Since the thickness of the dense surface layer is 50-100 μm, a layer that is too thin (<50 μm) cannot completely cover the filler, while a layer that is too thick (>100 μm) causes a surge in hot-pressing energy consumption; this range balances surface quality and cost.
[0023] In one embodiment, step S1 includes: Step S11: The high-filled polymer hollow board is placed in a two-roller hot pressing system, and the high-filled polymer hollow board is hot-pressed by the hot pressing rollers. The surface of the hot pressing rollers is coated with polytetrafluoroethylene (PTFE). The roller surface temperature is 10-15°C below the melting temperature of the substrate polymer, the pressure is controlled at 0.5-1.2 MPa, and the contact time is 3-8 seconds. The thickness of the PTFE coating is 0.1-0.3 mm. In this embodiment, the two-roller hot pressing system is a known structure and will not be described in detail here. Because the roller surface temperature is 10-15°C below the melting temperature of the substrate polymer, a dense surface layer is formed without causing excessive deformation or overheating of the substrate. The PTFE coating on the hot pressing rollers prevents material sticking to the rollers and ensures uniform heat conduction. Because the pressure is controlled at 0.5-1.2 MPa, the critical pressure densifies the surface layer without crushing the hollow structure.
[0024] Step S12: The roller spacing is dynamically adjusted by the servo pressure control system to form a dense surface layer with a thickness of 50~100μm on the surface of the high-fill polymer hollow board; wherein the surface roughness Ra of the dense surface layer is ≤0.8μm; in this embodiment, the servo pressure control system is a known technology and will not be described in detail here.
[0025] Step S13 involves rapidly cooling and shaping the hot-pressed high-fill polymer hollow board using a water-cooled roller. The cooling water temperature of the water-cooled roller is 15-25°C, and the cooling rate is ≥50°C / s. In this embodiment, the cooling water flow rate of the water-cooled roller is 10-15 L / min, and the temperature difference is controlled to ≤2°C. This rapid cooling process quickly lowers the material temperature, suppresses internal stress accumulation through phase change control, effectively shapes a dense surface layer, and prevents substrate deformation or uneven cooling caused by sudden temperature changes.
[0026] It should be noted that by precisely controlling the hot-pressing temperature, pressure, and contact time, a uniform, dense surface layer of 50-100 μm thickness is formed, significantly improving the surface quality of the high-filled polymer hollow board, enhancing its surface hardness and wear resistance, and extending its service life. The servo pressure control system dynamically adjusts the roller spacing to ensure the uniformity of the dense surface layer and a surface roughness ≤0.8 μm, greatly improving the adhesion and coating effect of the polymer surface coating and avoiding uneven coating and peeling. The water-cooled roller quenching in step S13 rapidly stabilizes the dense surface layer and prevents surface cracks or deformation caused by uneven cooling, ensuring the geometric stability and surface quality of the high-filled polymer hollow board. The combination of dual-roller hot pressing and the servo pressure control system allows the entire hot-pressing process to be completed efficiently and precisely, reducing human error and improving consistency and reliability in mass production.
[0027] Step S2 involves plasma cleaning of the hot-pressed high-fill polymer hollow plate to enhance its surface energy.
[0028] In one embodiment, step S2 specifically includes: The hot-pressed high-fill polymer hollow plate is placed in an atmospheric pressure plasma treatment device, and its surface is cleaned with argon plasma using a rotating electrode structure. The argon flow rate is 20-50 L / min, the plasma power is 800-1200 W, the treatment distance is 5-10 mm, and the treatment time is 30-90 s. In this embodiment, the atmospheric pressure plasma treatment device is a known device and will not be described in detail here. Unlike traditional fixed electrodes, the rotating electrode rotates at 10-30 rpm, with an electrode spacing fluctuation ≤0.1 mm. The rotating electrode can solve the problem of uniformity in three-dimensional curved surface treatment, ensuring surface energy fluctuation ≤5%. To prevent oxidation of the dense layer surface from affecting the plasma treatment effect, the process interval between steps S1 and S2 is less than or equal to 30 s.
[0029] Between step S2 and step S3, the following is also included: A grafting reaction is carried out by introducing a mixed gas of acrylic acid and maleic anhydride into the plasma treatment area to achieve a surface energy ≥50 mN / m for the high-fill polymer hollow plate after the reaction. The volume ratio of acrylic acid to maleic anhydride is 3:1, and the reaction time is 60–180 s. In this embodiment, acrylic acid provides carboxylic acid groups, and maleic anhydride enhances the crosslinking density; through their synergistic effect, a stable chemically active layer is formed. To suppress excessive oxidation, 0.5–1 vol% nitrogen gas can be incorporated into the mixed gas.
[0030] The surface state of the treated high-filled polymer hollow plate is monitored in real time using an online surface energy analyzer. The plasma power and gas flow rate are dynamically adjusted to control the surface roughness Ra of the high-filled polymer hollow plate within the range of 50~200 nm. In this embodiment, the online surface energy analyzer is a known device and will not be described in detail here.
[0031] It should be noted that the plasma cleaning treatment in step S2 effectively increases the surface energy of the high-filled polymer hollow board to ≥50mN / m, enhances the adhesion of subsequent coatings or adhesives, reduces the risk of coating peeling, and ensures the stability of the high-filled polymer hollow board in various applications. Plasma cleaning removes impurities and contaminants from the polymer surface, improving surface cleanliness and providing an ideal surface foundation for subsequent processing (such as coating and bonding). By monitoring and adjusting the plasma power and gas flow rate using an online surface energy detector, the surface roughness Ra of the high-filled polymer hollow board is maintained within the range of 50~200nm. This precise control both enhances surface energy and avoids excessive roughening, ensuring coating adhesion and uniformity in subsequent processing. Real-time monitoring and adjustment of processing parameters ensure consistent processing results for each batch of products, guaranteeing product quality stability during large-scale production.
[0032] Step S3 involves coating the surface of the plasma-cleaned high-fill polymer hollow board with a nanocomposite primer to obtain a first coating with a thickness of 5-8 μm. The nanocomposite primer comprises an epoxy-polyurethane hybrid resin and nano-silica modified with a silane coupling agent. To prevent contaminant adsorption on the active surface of the high-fill polymer hollow board, the process interval between steps S2 and S3 is less than or equal to 5 minutes, and nitrogen gas is used for protection.
[0033] In one embodiment, step S3 includes: Step S31: Silane coupling agent modified nano-silica with a particle size of 20-50 nm is dispersed in a solvent at a ratio of 3-5 wt% to form a nano-composite primer; the solid content of the epoxy-polyurethane hybrid resin is 40-50%; in this embodiment, the silane coupling agent can be γ-aminopropyltriethoxysilane (KH550), and the plasma cleaning time is 2-4 h.
[0034] Step S32: An ultrasonic-electrostatic atomization spraying device is used to coat the surface of the cleaned high-fill polymer hollow board with a nano-composite primer, forming a first coating with a thickness of 5-8 μm. The spraying voltage is 25-35 kV, the ultrasonic frequency is 25-30 kHz, and the spraying distance is 15-25 cm. The atomization angle is 60-80°, and the atomization pressure is 0.2-0.4 MPa. In this embodiment, when the spraying voltage is less than 25 kV, atomization is insufficient and the coating thickness deviation is greater than 15%; when the spraying voltage is greater than 35 kV, uneven spraying is likely to occur. To ensure that the coating edge thickness difference is less than 5%, the atomization angle of the ultrasonic-electrostatic atomization spraying is 60-80°, and the atomization pressure is 0.2-0.4 MPa.
[0035] Step S33: After applying the nano-composite primer, the first coating is leveled to eliminate ripples or bubbles generated during spraying. The leveling temperature is 40-60°C, the leveling time is 30-60 seconds, and the humidity is controlled at 30-50% RH. In this embodiment, when the leveling temperature is below 40°C, more solvent residue is left; when the leveling temperature is above 60°C, pre-crosslinking is easily triggered, thus affecting the UV curing efficiency of the subsequent step S4.
[0036] It should be noted that in step S31, the formation of a nanocomposite primer using silane coupling agent-modified nano-silica and epoxy-polyurethane hybrid resin can significantly improve the elastic modulus of the coating and enhance its mechanical properties (such as hardness and rigidity) without affecting its toughness. In step S32, the ultrasonic-electrostatic atomization spraying technology allows for precise control of the coating thickness and uniformity, avoiding thickness deviations and unevenness issues that may occur with traditional spraying methods, thus ensuring coating stability. Strict control of parameters such as voltage, frequency, atomization angle, and atomization pressure during the spraying process ensures coating quality. In step S33, leveling treatment of the first coating eliminates ripples or bubbles generated during spraying, ensuring a smooth and uniform coating surface, thereby improving the coating's appearance quality. Precise control of leveling temperature, time, and humidity avoids solvent residue or premature crosslinking, ensuring the UV curing efficiency and effect of the subsequent step S4, further improving the overall performance of the coating.
[0037] It should also be noted that steps S33 and S2 have a synergistic effect. After plasma cleaning, the high surface energy of the surface-enhancing primer improves wettability, and the leveling treatment allows the resin to spread fully, covering the nanoscale rough structure (50~200nm), forming a composite interface of mechanical interlocking and chemical bonding. If the leveling treatment in step S33 is skipped, direct curing will lead to the aggregation of nano-silica particles, reducing adhesion. Step S33 lays the foundation for step S4. After leveling, the coating forms a uniform "wet film-air" interface, and the heat transfer is uniform during the pre-curing (80℃) in step S41, avoiding stress concentration caused by local crosslinking density differences. The leveling treatment in step S33 provides an ideal substrate for the functional topcoat in step S5. The surface roughness Ra of the leveled primer is ≤0.1μm, ensuring the stacking accuracy of subsequent multilayer functional coatings. The leveling treatment in step S33 also ensures the quality of the laser microstructure processing in the subsequent step S6. The uniform first coating ensures consistent laser energy absorption, avoiding deviations in the depth of the microstructure due to uneven coating thickness. Step S4 involves a two-stage curing process for the first coating, which includes pre-curing and UV curing. In this embodiment, to prevent moisture absorption by the coating from causing curing defects, the process interval between steps S3 and S4 is less than or equal to 10 minutes, and nitrogen gas is used for protection.
[0038] In one embodiment, step S4 includes: Step S41 involves pre-curing the high-filled polymer hollow board coated with the first coating using a hot air circulating curing chamber to achieve a curing degree of 70-80% for the nanocomposite primer. The curing temperature is 80℃±2℃, and the curing time is 1.5-2.5 min. In this embodiment, the hot air circulating curing chamber is a well-known device in the art and will not be described in detail here. To prevent turbulence on the coating surface, the air velocity during hot air circulation is 0.5-1.0 m / s, and the angle between the airflow direction and the board is 30-45°. The pre-curing treatment activates the initial cross-linking of the epoxy resin, avoiding stress cracking that occurs with direct UV curing. Because the pre-curing temperature is lower than the initial Tg value of the epoxy-polyurethane hybrid resin (approximately 75℃), the rebound of the leveling structure is avoided.
[0039] Step S42: Use a dual-wavelength UV light source to perform UV curing treatment on the pre-cured first coating to achieve a final curing degree of ≥95% for the first coating; The first curing stage uses a UV light source with a wavelength of 365nm and an energy density of 200~300mJ / cm². 2 The irradiation time is 5-8 seconds; the second curing stage uses a UV light source with a wavelength of 420 nm and an energy density of 500-800 mJ / cm². 2 The irradiation time is 10-15 seconds. In this embodiment, to achieve better cross-linking, the energy density ratio between the 365nm UV light source and the 420nm UV light source is 1:2.5-3.0. The 365nm UV light source initiates rapid surface cross-linking, while the 420nm UV light source promotes complete deep curing, solving the technical problem of incomplete curing with traditional single-wavelength methods.
[0040] It should be noted that the two-stage curing method (pre-curing and UV curing) significantly improves the curing degree of the coating. In the pre-curing stage, hot air circulation achieves 70-80% curing of the nanocomposite primer, avoiding defects such as turbulence or stress cracking on the coating surface caused by direct UV curing. The UV curing stage uses a dual-wavelength UV light source, effectively improving the cross-linking degree of the coating and ensuring a final curing degree greater than or equal to 95%. In step S42, the use of a dual-wavelength UV light source not only rapidly achieves surface cross-linking (365nm) but also effectively promotes complete curing of the deeper layers of the coating (420nm). This dual-wavelength curing scheme overcomes the incomplete cross-linking problem present in traditional single-wavelength curing methods, ensuring excellent durability and performance of the coating.
[0041] Step S5: Apply a functional topcoat to the surface of the cured first coating to obtain a functional coating, and then cure the functional coating; wherein, the functional coating includes a second coating, a third coating, and a fourth coating attached sequentially. In this embodiment, to prevent interface contamination, the process interval between steps S4 and S5 is less than or equal to 15 minutes.
[0042] In one embodiment, step S5 includes: Step S51: Fluorinated polyurethane acrylate resin is electrostatically sprayed onto the surface of the cured first coating to form a second coating with a thickness of 10-15 μm. The spraying voltage is 40-60 kV, the spraying flow rate is 50-80 mL / min, and the coating is allowed to stand and level for 1-2 minutes after spraying. In this embodiment, the second coating provides low surface energy protection, and electrostatic spraying ensures density. Because the electrostatic spraying voltage is 40-60 kV, a uniform electric field (field strength 3-5 kV / cm) is formed, controlling the fluorinated resin droplet size to 10-20 μm.
[0043] In step S52, nano-Al2O3-reinforced silicone-modified resin is spin-coated onto the surface of the second coating to form a third coating with a thickness of 8-12 μm, and then the third coating is subjected to thermosetting treatment. The spin-coating speed is 800-1200 rpm, the curing temperature is 100-120℃, and the curing time is 3-5 min. In this embodiment, to prevent uneven thickness of the second coating, the acceleration of the spin-coating process is 200-400 rpm / s, and the deceleration rate is 100-200 rpm / s. In this embodiment, the third coating is a high-hardness intermediate layer, matched to the thermal expansion coefficient of the primer. The silicone-modified resin contains bifunctional groups (such as vinyl + epoxy groups), and thermosetting preferentially completes the condensation reaction, retaining some double bonds for UV curing. Through thermosetting in step S52, the nano-Al2O3-reinforced silicone-modified resin completes physical crosslinking and preliminary chemical crosslinking, forming a rigid framework structure. Step S53: Photochromic titanium dioxide / graphene composite slurry is applied to the surface of the third coating through slit extrusion to form a fourth coating with a thickness of 5~8μm; wherein the coating gap is 50~100μm and the coating speed is 2~4m / min; in this embodiment, the ratio of rutile TiO2 to anatase in the photochromic slurry is 7:3, and the graphene sheet diameter is 1~5μm.
[0044] Step S54 yields a functional coating comprising a second, third, and fourth layer. The functional coating is then subjected to gradient curing using a three-wavelength UV light source. In this embodiment, gradient curing is used to deeply crosslink and activate the functions of the multilayer functional coatings (second to fourth layers), constructing a gradient network structure. In this embodiment, electrostatic spraying, spin coating, and slot extrusion are all well-known techniques in the art and will not be described in detail here.
[0045] It should be noted that the functionality of the coating is significantly improved by applying the second, third, and fourth coatings layer by layer. The second coating provides low surface energy protection, the third coating is a high-hardness intermediate layer that enhances the coating's wear resistance and mechanical strength, and the fourth coating introduces photochromic properties, improving the coating's environmental adaptability and intelligent responsiveness. In step S53, the thermosetting treatment of the third coating and the crosslinking of the silicone-modified resin form a rigid framework structure, which enhances the coating's hardness, wear resistance, and adaptability to the external environment. In step S54, the photochromic properties of the fourth coating enable the coating to respond to changes in ambient light, providing intelligent adjustment capabilities and further enhancing the coating's practicality. Gradient curing with a three-wavelength UV light source ensures that different functional layers in the coating achieve functional activation while undergoing deep crosslinking. The gradient curing treatment in step S54 forms a layered structure coating, improving the overall performance and stability of the coating and giving it better durability, reactivity, and multifunctionality.
[0046] Specifically, step S54 includes: Step S541, the first stage of curing uses a UV light source with a wavelength of 395nm and an energy density of 800~1000mJ / cm². 2 The irradiation time is 5-8 seconds, and the surface of the fourth coating is vertically irradiated. In this embodiment, a UV light source with a wavelength of 395nm triggers rapid cross-linking of the fluorinated polyurethane acrylate resin (second coating) surface layer, inhibiting the oxygen inhibition effect; simultaneously activating the partial transformation of the anatase phase of photochromic titanium dioxide to the rutile phase (XRD detection shows that the rutile phase accounts for ≥60%), enhancing optical stability.
[0047] In step S542, the second curing stage switches to a UV light source with a wavelength of 365nm and an energy density of 1200~1500mJ / cm². 2 The irradiation time is 10-15s, and the irradiation is performed at a 45° tilt angle. In this embodiment, a UV light source with a wavelength of 365nm penetrates the fourth coating, strengthens the deep cross-linking of the nano-Al2O3-enhanced organosilicon layer (the third coating), and the double bond conversion rate is greater than or equal to 95% (FTIR detection of C=C peak attenuation rate). This promotes the interfacial bonding between graphene and titanium dioxide (Raman spectrum D / G peak ratio decreases from 1.2 to 0.8), and improves the conductivity of the coating.
[0048] Step S543: The third stage of curing switches to a UV light source with a wavelength of 420nm and an energy density of 500~700mJ / cm². 2The irradiation time is 8-12 seconds, and the focused spot diameter is 2-5 mm for local supplemental lighting. In this embodiment, the crystal structure of the photochromic material is stabilized (the phase transition temperature is increased by 20°C according to DSC detection) to ensure that the color change response time is ≤5 seconds; the internal stress generated by gradient curing is eliminated (the stress value is ≤5 MPa according to photoelastic detection) to prevent interlayer delamination.
[0049] It should be noted that the rapid cross-linking of the second coating surface is activated by a 395nm wavelength UV light source, which simultaneously promotes the transformation of the anatase phase to the rutile phase in photochromic titanium dioxide, enhancing the optical stability of the coating and ensuring that its color-changing effect does not degrade during long-term use. The third coating is further cross-linked by a 365nm wavelength UV light source, achieving a double bond conversion rate of over 95%, improving the coating's hardness and durability. Simultaneously, it promotes interfacial bonding between graphene and titanium dioxide, enhancing the coating's conductivity. The 420nm wavelength UV light source stabilizes the crystal structure of the photochromic material and increases the phase transition temperature, enabling the coating to respond quickly to changes in ambient light and improving its intelligent adjustment capabilities. This three-stage curing process combines the advantages of different wavelengths of UV light, not only optimizing the curing effect of each coating but also activating multiple functions such as photochromism and conductivity, resulting in a final coating with better intelligence and adaptability, capable of coping with different environmental changes.
[0050] Step S6 involves laser processing of the functional coating to create microstructures and melting ripples on its surface. To prevent moisture absorption and degradation of the photochromic layer, the process interval between steps S5 and S6 is less than or equal to 30 minutes, and the ambient humidity is controlled to be less than or equal to 40%RH.
[0051] In one embodiment, step S6 includes: Step S61 involves using a femtosecond fiber laser to laser-etch the functional coating, forming a periodic array of micron-sized grooves on the surface of the fourth coating. The laser power is 5–10 W, the repetition rate is 100–200 kHz, the scanning speed is 1000–1500 mm / s, and the spot diameter is 10–20 μm. The groove depth is 5–15 μm, the width is 20–50 μm, and the spacing between adjacent grooves is 50–100 μm. In this embodiment, a laser power below 5 W cannot penetrate the fourth coating, while a laser power above 10 W can easily induce plasma shielding.
[0052] Step S62: Switch the femtosecond fiber laser to quasi-continuous mode and use a flat-top laser spot to perform melting and regeneration treatment on the engraved area, forming nanoscale melting ripples with a height difference ≤0.5μm; wherein the laser power density is 2~5×10 4 W / cm 2The scanning speed is 200~400mm / s, the pulse frequency is 1~10kHz, and the duty cycle is 30~50%; the melting scanning path is set to a spiral involute with a pitch of 100μm.
[0053] Step S63 involves introducing a helium / nitrogen mixed cooling gas to cool the laser-processed functional coating; wherein the volume ratio of helium to nitrogen is 1:4. In this embodiment, the femtosecond fiber laser is a well-known structure in the art and will not be described in detail here. Using a helium / nitrogen mixed gas for cooling helps to rapidly reduce the coating temperature after laser processing, prevent coating damage caused by overheating, and maintain the stability of the coating.
[0054] It should be noted that the laser engraving process in step S61, which forms a periodic array of micron-sized grooves on the surface of the fourth coating, can effectively enhance the functionality of the coating, such as increasing surface friction, improving coating adhesion, and enhancing optical properties (e.g., increasing surface scattering). The laser melting and regeneration process in step S62, which forms nanoscale melting ripples, further optimizes the surface morphology of the coating. These nanoscale micro-ripples not only help enhance the physical properties of the coating (such as wear resistance and hardness) but also improve its optical effects, especially in applications requiring reflected or scattered light.
[0055] Working Principle: This invention provides a surface treatment method and apparatus for high-filled polymer hollow boards. Step S1, hot pressing, forms a dense layer with a thickness of 50-100 μm on the surface of the high-filled polymer hollow board, significantly reducing surface porosity, improving the mechanical strength and surface smoothness of the substrate, and providing a uniform and stable adhesion substrate for subsequent coatings. Step S2, plasma cleaning, significantly increases the surface energy of the high-filled polymer hollow board, enhancing the adhesion between the coating and the substrate, providing a good surface foundation for subsequent application of a nanocomposite primer, thereby improving the durability and adhesion of the coating. In step S3, the application of the nanocomposite primer not only further enhances the surface corrosion resistance and oxidation resistance but also helps improve the overall performance of the high-filled polymer hollow board. Step S4, a two-stage curing process, effectively avoids uneven coating surface and bubble problems, ensuring the degree of curing and improving the durability and performance stability of the coating. In step S5, the application of a multi-layered functional coating enables the high-filled polymer hollow board to possess multiple functions during use, increasing the product's application range and market competitiveness. In step S6, the microstructure and melting ripples after laser processing not only improve the visual effect of the coating but also enhance the physical properties of the coating surface (such as the coefficient of friction and optical properties), thereby improving the applicability of the high-filled polymer hollow board in special application fields. Therefore, the present invention solves the technical problem of insufficient adhesion of high-filled polymer hollow boards in the prior art.
[0056] Example 2: This invention provides a surface treatment apparatus for highly filled polymer hollow boards, applicable to the surface treatment method for highly filled polymer hollow boards as described in Embodiment 1. Figure 2 As shown, it includes a dual-roller hot pressing module, a plasma cleaning module, a coating module, a curing module, a functional processing module, and a laser processing module; wherein, the dual-roller hot pressing module includes a hot pressing roller and a cold pressing roller; The twin-roller hot pressing module is used to perform hot pressing on the high-filled polymer hollow board; the plasma cleaning module is used to perform plasma cleaning on the high-filled polymer hollow board after hot pressing; the coating module is used to coat the surface of the plasma-cleaned high-filled polymer hollow board with a nano-composite primer to obtain a first coating layer; and the curing module is used to cure the first coating layer. The functional processing module is used to coat the surface of the cured first coating with a functional topcoat to obtain a functional coating, and then cures the functional coating. The laser processing module is used to perform laser processing on the functional coating, so that the surface of the functional coating forms microstructures and melting ripples. In this embodiment, the transfer of the high-filling polymer hollow board between the modules can be achieved by a conveyor belt or a robotic arm.
[0057] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A surface treatment method for a highly filled polymer hollow plate, characterized in that, include: Step S1: Provide a high-filled polymer hollow board and perform hot pressing on the high-filled polymer hollow board to form a dense surface layer with a thickness of 50~100μm. Step S2: The hot-pressed high-fill polymer hollow plate is subjected to plasma cleaning to improve the surface energy of the high-fill polymer hollow plate. Step S3: A nanocomposite primer is coated on the surface of the plasma-cleaned high-fill polymer hollow plate to obtain a first coating with a thickness of 5~8μm; wherein, the nanocomposite primer includes epoxy-polyurethane hybrid resin and nano-silica modified with silane coupling agent. Step S4: Perform a two-stage curing process on the first coating; wherein the two-stage curing includes pre-curing and UV curing; Step S5: Apply a functional topcoat to the surface of the cured first coating to obtain a functional coating, and then cure the functional coating; wherein the functional coating includes a second coating, a third coating, and a fourth coating attached in sequence. Step S6: Perform laser processing on the functional coating to form microstructures and melting ripples on the surface of the functional coating.
2. The surface treatment method for a high-filling polymer hollow plate according to claim 1, characterized in that, Step S1 includes: Step S11: The high-filled polymer hollow board is placed in a two-roller hot pressing system and hot-pressed by the hot pressing rollers; wherein, the surface of the hot pressing rollers is coated with polytetrafluoroethylene, the roller surface temperature is 10~15°C below the melting temperature of the substrate polymer, the pressure is controlled at 0.5~1.2MPa, and the contact time is 3~8s. Step S12: The roller spacing is dynamically adjusted by a servo pressure control system to form a dense surface layer with a thickness of 50~100μm on the surface of the high-fill polymer hollow plate.
3. The surface treatment method for a high-filling polymer hollow plate according to claim 2, characterized in that, After step S12, step S1 further includes: Step S13: The hot-pressed high-filled polymer hollow board is rapidly cooled and shaped using a water-cooled roller; wherein the cooling water temperature of the water-cooled roller is 15~25℃ and the cooling rate is ≥50℃ / s.
4. The surface treatment method for a high-filling polymer hollow plate according to any one of claims 1 to 3, characterized in that, Step S2 specifically includes: The hot-pressed high-fill polymer hollow plate is placed in an atmospheric pressure plasma treatment device to perform argon plasma cleaning on its surface.
5. The surface treatment method for a high-filling polymer hollow plate according to any one of claims 1 to 3, characterized in that, Step S3 includes: Step S31: Silane coupling agent-modified nano-silica with a particle size of 20-50 nm is dispersed in a solvent at a ratio of 3-5 wt% to form a nano-composite primer; the epoxy-polyurethane hybrid resin has a solid content of 40-50%. Step S32: The nanocomposite primer is applied to the surface of the plasma-cleaned high-fill polymer hollow plate using an ultrasonic-electrostatic atomization spraying device to form a first coating with a thickness of 5~8μm.
6. The surface treatment method for a high-filling polymer hollow plate according to claim 5, characterized in that, Following step S32, the method further includes: Step S33: After the nano-composite primer is applied, the first coating is leveled to eliminate ripples or bubbles generated during the spraying process.
7. The surface treatment method for a high-filling polymer hollow plate according to claim 1, characterized in that, Step S4 includes: Step S41: The high-filled polymer hollow board coated with the first coating is pre-cured using a hot air circulating curing chamber to achieve a curing degree of 70-80% for the nano-composite primer. Step S42: Use a dual-wavelength UV light source to perform UV curing treatment on the pre-cured first coating to make the final curing degree of the first coating ≥95%.
8. The surface treatment method for a high-filling polymer hollow plate according to claim 1, characterized in that, Step S5 includes: Step S51: Electrostatically spray fluorinated polyurethane acrylate resin onto the surface of the cured first coating to form a second coating with a thickness of 10~15μm. Step S52: Spin-coat nano-Al2O3-reinforced organosilicon modified resin onto the surface of the second coating to form a third coating with a thickness of 8~12μm, and perform thermosetting treatment on the third coating. Step S53: Photochromic titanium dioxide / graphene composite slurry is applied to the surface of the third coating through slit extrusion to form a fourth coating with a thickness of 5~8μm. Step S54: A functional coating including a second coating, a third coating, and a fourth coating is obtained. The functional coating is then subjected to gradient curing treatment using a three-wavelength UV light source.
9. The surface treatment method for a high-filling polymer hollow plate according to claim 1, characterized in that, Step S6 includes: Step S61: A femtosecond fiber laser is used to laser-etch the functional coating to form a periodic array of micron-sized grooves on the surface of the fourth coating. Step S62: Switch the femtosecond fiber laser to quasi-continuous mode and use a flat-top spot to perform melting and regeneration treatment on the engraved area to form nanoscale melting ripples with a height difference ≤0.5μm; Step S63: A helium / nitrogen mixed cooling gas is introduced to cool the functional coating after laser processing.
10. A surface treatment apparatus for a highly filled polymer hollow board, applied to the surface treatment method for a highly filled polymer hollow board as described in any one of claims 1 to 9, characterized in that, It includes a dual-roller hot pressing module, a plasma cleaning module, a coating module, a curing module, a functional processing module, and a laser processing module; wherein, the dual-roller hot pressing module includes a hot pressing roller and a cold pressing roller; The dual-roller hot pressing module is used to perform hot pressing on the high-filled polymer hollow board; the plasma cleaning module is used to perform plasma cleaning on the high-filled polymer hollow board after hot pressing; the coating module is used to coat the surface of the plasma-cleaned high-filled polymer hollow board with a nano-composite primer to obtain a first coating layer; and the curing module is used to cure the first coating layer. The functional processing module is used to coat the surface of the first coating after curing with a functional topcoat to obtain a functional coating, and to cure the functional coating; the laser processing module is used to perform laser processing on the functional coating to form microstructures and melting ripples on the surface of the functional coating.